2000
DOI: 10.1007/pl00000650
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog signaling pathway in vertebrate epithelial appendage morphogenesis: perspectives in development and evolution

Abstract: Vertebrate epithelial appendages are elaborate topological transformations of flat epithelia into complex organs that either protrude out of external (integument) and internal (oral cavity, gut) epithelia, or invaginate into the surrounding mesenchyme. Although they have specific structures and diverse functions, most epithelial appendages share similar developmental stages, including induction, morphogenesis, differentiation and cycling. The roles of the SHH pathway are analyzed in exemplary organs including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 62 publications
(66 reference statements)
3
75
0
Order By: Relevance
“…These data extend previously documented roles for hedgehog signaling in dermal bone development (29,30) and suggest that this pathway plays an important role in polarizing dermal bone development along a proximal-distal axis. It is well established that hedgehog signaling is critical for the proper patterning and polarization of several organs in various animal taxa (32)(33)(34)(35)(36)(37), but here a similar role has been documented for bone development. The extent to which hedgehog-mediated outgrowth of other dermal bones (e.g., RA) has influenced species-specific differences in craniofacial shape would be a fruitful area of future investigation.…”
Section: Manipulation Of Hedgehog Pathway Signaling Affects Bone Devementioning
confidence: 75%
“…These data extend previously documented roles for hedgehog signaling in dermal bone development (29,30) and suggest that this pathway plays an important role in polarizing dermal bone development along a proximal-distal axis. It is well established that hedgehog signaling is critical for the proper patterning and polarization of several organs in various animal taxa (32)(33)(34)(35)(36)(37), but here a similar role has been documented for bone development. The extent to which hedgehog-mediated outgrowth of other dermal bones (e.g., RA) has influenced species-specific differences in craniofacial shape would be a fruitful area of future investigation.…”
Section: Manipulation Of Hedgehog Pathway Signaling Affects Bone Devementioning
confidence: 75%
“…JAG1 and DLL1 participate in the notch signaling pathway, which affects the implementation of differentiation, proliferation, and apoptotic programs, providing a general developmental tool to influence organ formation and morphogenesis (6,52). In addition, IPA revealed that copper could significantly modulate sonic hedgehog signaling, which is critical in vertebrate development (14). These results suggest that the modulation of notch and sonic hedgehog signaling may be components of molecular mechanisms underlying copper-induced developmental abnormalities.…”
Section: Continuedmentioning
confidence: 83%
“…There were also enriched GO categories that mapped to specific treatment conditions: oxygen and ROS metabolism and IGF binding (400 M, 8 h); ubiquitin-protein ligase activity (600 M, 8 h); endosome organization and (2) Lipid transport (8)* Cholesterol binding (2) Lipoprotein metabolism (6)* Cholesterol metabolism (4) Acyl-CoA binding (3) Hemoglobin binding (2) Alcohol metabolism (19) Platelet activation (2) Amine metabolism (26) Regulation of body fluids (4) Chromatin assembly (6) Serine-type endopeptidase inhibitor activity (5) Creatine biosynthesis (2) Wound healing (4) Deoxyribonucleotide biosynthesis ( (2) B cell-mediated immunity (7) Hemoglobin binding (2) Complement activation (7) Lipid binding (9) Creatine biosynthesis (2) Cytolysis (4) Hormone metabolism (10) Lipid transporter activity (13) Nickel ion binding (2) Oxidoreductase activity (52) Positive regulation of immune response (7) Serine-type peptidase activity (14) Xenobiotic metabolism (5) Shown are Gene Ontology (GO) categories with P Յ 0.005. Responsive genes were 2-fold downregulated with FDR P Յ 0.05.…”
Section: Go Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…Quantitation of these complex elements of tissue pattern is essential to establish a ruler against which to accurately compare perturbances in the system. The intestinal mesenchymal clusters have several similarities to the mesenchymal condensates involved in the patterning of hair, teeth, tongue papillae, feathers, and hair follicles (13,26,(33)(34)(35)(36)(37)(38)(39). Like the dermal condensates associated with feather formation in the chick, villus clusters first arise in anterior and dorsal midline regions and then spread posteriorly and laterally (33).…”
Section: Discussionmentioning
confidence: 99%